TRADISI RUWATAN BAGI MASYARAKAT DIENG - Widyatwati, Ken (Faculty of Humanities, Diponegoro University, 2012)
The narrative or a myth is not only one story, but it have a meaning and structure. The structure of myth is representation form the society, who to support. Structure or model to become representation from the society to exist in stage unconscious, and only to be looking for with structuralism Levi-Straus Analysis. Exorcism Ritual for Dieng Society is a folklore wich Dieng society. Exorcism Ritual for Dieng Society is not ritual content, but it have many contents be trusted by community, The aim of this research is description of Exorcism Ritual for Dieng Society are component Identification, and the content of myth. This Ritual perform every year the date in one Sura in Javanese Callender. Time is 05.00-14.00 am. The place is Bale Kambang Lake in Dieng Banjarnegara, Central Java. The content of Exorcism Ritual for Dieng Society is place, time, instrument, ritual offering, prayer and myth. This myth is Rambut Gembel and Exorcism Ritual of Rambut Gembel cut. Keywords: Exorcism, Ritual, Exorcism Ritual Prosesion of Rambut Gembel Cut